2000
DOI: 10.1111/j.1741-3737.2000.00123.x
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Paternal and Maternal Acceptance and Rural African American and European American Youths' Psychological Adjustment

Abstract: This study explores the following question: Are rural African American and European American youths' experiences of paternal and maternal acceptance equally related to their self-reported psychological adjustment, or do youths' experiences of paternal acceptance account for an independent portion of the variance in psychological adjustment, over and above the portion of variance explained by their experiences of maternal acceptance? This study also explores possible social-class, age, gender, and paternal-resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
1
13

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 24 publications
4
39
1
13
Order By: Relevance
“…T-test results of acceptance-rejection level according to age showed that acceptance level did not differentiate according to child's age. This result is in accordance with the results of the other studies investigating acceptance level according to age (Erkman & Rohner, 2006;Veneziano, 2000).…”
Section: Resultssupporting
confidence: 83%
“…T-test results of acceptance-rejection level according to age showed that acceptance level did not differentiate according to child's age. This result is in accordance with the results of the other studies investigating acceptance level according to age (Erkman & Rohner, 2006;Veneziano, 2000).…”
Section: Resultssupporting
confidence: 83%
“…Many of these studies conclude that father/paternal love explains a unique and independent portion of the variance in specific child outcomes over and above the portion explained by maternal love (Ahmed et al, 2012;Carrasco & Rohner, 2013;Rohner & Carrasco, 2014;Veneziano, 2003). Other studies conclude that paternal love is sometimes the sole significant predictor of specific child outcomes (Rohner & Veneziano, 2001).…”
Section: The Importance Of Father Lovementioning
confidence: 99%
“…Substantial evidence in many of the foregoing classes of study suggests that father love (acceptance-rejection) is often as strongly implicated as mother love in the development of behavioral and psychological problems as well as in the development of offspring's sense of health and well-being (Rohner, 1998;Rohner & Veneziano, 2001;Veneziano, 2000Veneziano, , 2003. Studies supporting this conclusion tend to deal with the following issues among children, adolescents, and adults: (1) personality and psychological adjustment problems (Ahmed, Rohner, & Carrasco, 2012;Amato, 1994;Dominy, Johnson, & Koch, 2000;Khaleque & Rohner, 2011;Komarovsky, 1976;Stagner, 1938); (2) mental illness (Akun, 2016;Barrera Jr. & Garrison-Jones, 1992;Lefkowitz & Tesiny, 1984); (3) psychological health and well-being (Amato, 1994); (4) conduct disorder (Eron, Banta, Walder, & Laulicht, 1961;Putnick et al, 2014); (5) substance abuse (Brook & Brook, 1988;Emmelkamp & Heeres, 1988); (6) delinquency (Andry, 1962); (7) prosocial behavior (Putnick et al, 2014); (8) children's social competence (Putnick et al, 2014); and (9) school performance (Putnick et al, 2014).…”
Section: The Importance Of Father Lovementioning
confidence: 99%
“…That means primary school graduate mothers neglect their 6-12 years children more compared to others. Erkan and Toran assert in their study that as mothers' educational level decreases, their rejection behaviors increase and vice versa [14] (13). In many other studies, it has been put forth that increase in mothers' educational levels rises the percentage of their acceptive behaviors and decrease in their educational levels increase their rejective-negative behaviors towards their children [22,23,20,3,24].…”
Section: Discussionmentioning
confidence: 99%
“…In Erkman and Rohner's study [12] that investigates the possible cahnge of parental acception or rejection in terms of age of the children, it was deduced that mothers' acceptance-rejection behaviors did not differentiate according to ages of children. The study carried out by Veneziano [13] namely "Perceived Paternal and Maternal Acceptance and Psychological Adaptation of Rural Afro-American and European-American Youngsters" emphasised that there were not any relations between mothers' acceptance-rejection of their children and age of the children.…”
Section: Discussionmentioning
confidence: 99%